2008
DOI: 10.1098/rsbl.2008.0131
|View full text |Cite
|
Sign up to set email alerts
|

A label of health: a previous immune challenge is reflected in the expression of a female plumage trait

Abstract: Studies of ornaments as indicators of individual quality have hitherto focused on males, while studies of female ornaments have been almost absent. However, females within the same species may show large variation in both outer appearance and individual quality. We experimentally examined the effect of an immune challenge on the size of white fringes in the wing feathers produced one to two months after the challenge in female common eiders ( Somateria mollissima ), a long-lived sea duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
13
2
Order By: Relevance
“…Female ornamentation has mainly been studied in birds (Amundsen 2000); some studies have found a connection between female ornaments and phenotypic quality (Møller 1993;Johnsen et al 1996;Jawor et al 2004), while others have not (Muma & Weatherhead 1989;Coervo et al 1996). Hanssen et al (2006Hanssen et al ( , 2008 suggested a connection between female ornamentation and phenotypic quality in female eider ducks (Somateria mollissima). These studies found that females with broader and brighter white wing bars had higher immunocompetence, lower mass loss during incubation and marginally larger clutches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female ornamentation has mainly been studied in birds (Amundsen 2000); some studies have found a connection between female ornaments and phenotypic quality (Møller 1993;Johnsen et al 1996;Jawor et al 2004), while others have not (Muma & Weatherhead 1989;Coervo et al 1996). Hanssen et al (2006Hanssen et al ( , 2008 suggested a connection between female ornamentation and phenotypic quality in female eider ducks (Somateria mollissima). These studies found that females with broader and brighter white wing bars had higher immunocompetence, lower mass loss during incubation and marginally larger clutches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, eider broodrearing tactics range from lone tending to brood care in female coalitions (Ö st et al 2003a). Hanssen et al (2006Hanssen et al ( , 2008 therefore proposed that female ornaments may be honest signals of individual quality used not only by courting males, but also in female-female interactions in brood-rearing coalitions.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of melanin expressed in white feathers or white parts of feathers has been shown to have a clear genetic component (Garant et al 2004) and to act as an indicator of phenotypic quality in several species (Potti and Merino 1996;Kose et al 1999;Ruusila et al 2001;Hanssen et al 2006Hanssen et al , 2008de Heij et al 2011). White patches may have evolved as a costly handicap of feather quality or as an amplifying handicap that reflects the individual's ability to cope with its lack of melanin without compromising survival (Hasson 1991, Fitzpatrick 1998, especially if expressed in flight feathers.…”
mentioning
confidence: 99%
“…Furthermore, in some species white rather than black coloration reflects quality (e.g. Hanssen et al 2006), suggesting that sometimes pale coloration is more costly to produce than dark coloration (Hanssen et al 2008). As a consequence, the signalling function of melanin-based traits remains controversial.…”
Section: Introductionmentioning
confidence: 99%